THE ENERGY COMPLEXES BASED ON SOLAR POWER PLANTS AND BATTERY ENERGY STORAGE SYSTEMS - Havrylenko, Yaroslav; Derii, Volodymyr (General Energy Institute of the National Academy of Sciences of Ukraine, 2025)
The direction of reducing greenhouse gas emissions into the atmosphere and the corresponding legislative framework in recent years in Ukraine have stimulated the development of renewable energy sources and the active installation of solar power plants. Due to the implementation of projects in the energy sector using solar power plants, the Unified Energy System of Ukraine requires new approaches to the construction of energy balancing complexes that can ensure its stability and flexibility. The more solar power plants are implemented and commissioned, the more systemic problems the Ukrainian energy sector faces due to the stochastic nature of their generation. One possible method of solving this problem is the creation of energy complexes that combine solar power plants with battery energy storage systems. The use of battery energy storage systems allows not only the smoothing of peak loads and stabilisation of the grid but also increases the efficiency of generated energy utilisation. This is particularly relevant given the growing demand for electricity and the need to reduce dependence on traditional energy resources. This article provides an overview of the main types of energy complex structures based on solar power plants and battery energy storage systems, analyzing their key advantages and disadvantages, as well as the factors influencing the choice of energy complex configuration depending on its purpose. The review and analysis show that for new projects, it is more reasonable to connect battery storage systems to solar power plants on the direct current side (DC coupled), allowing storage and utilisation of 1−4 % more electricity. On the other hand, energy complexes that use battery energy storage systems connected on the alternating current side (AC coupled) are more versatile, flexible, and convenient for upgrading existing solar power plants. Implementing cutting-edge technologies in energy storage and improving solar power generation forecasting will enable Ukraine’s energy system to become more resilient and reliable in the long term.